2007
DOI: 10.1038/nn2011
|View full text |Cite
|
Sign up to set email alerts
|

Polyglutamine domain modulates the TBP-TFIIB interaction: implications for its normal function and neurodegeneration

Abstract: Expansion of the polyglutamine (polyQ) tract in human TATA-box binding protein (TBP) causes the neurodegenerative disease spinocerebellar ataxia 17 (SCA17). It remains unclear how the polyQ tract regulates normal protein function and induces selective neuropathology in SCA17. We generated transgenic mice expressing polyQ-expanded TBP. These mice showed weight loss, progressive neurological symptoms and neurodegeneration before early death. Expanded polyQ tracts reduced TBP dimerization but enhanced the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
146
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(164 citation statements)
references
References 45 publications
14
146
0
Order By: Relevance
“…The pathogenic domain of mutant Huntington disease protein (httex1p) containing expanded polyQ repeats has also been found to interact with CREB-binding protein (17). ZEBRA functionally interacts with TATA box-binding protein, another polyQ-containing protein implicated in spinocerebellar ataxia 17 (61)(62)(63). Aggresome formation by the ZEBRA mutants reported in this study may be mediated by interactions with the same polyQ proteins that interact with WT ZEBRA.…”
Section: Discussionmentioning
confidence: 53%
“…The pathogenic domain of mutant Huntington disease protein (httex1p) containing expanded polyQ repeats has also been found to interact with CREB-binding protein (17). ZEBRA functionally interacts with TATA box-binding protein, another polyQ-containing protein implicated in spinocerebellar ataxia 17 (61)(62)(63). Aggresome formation by the ZEBRA mutants reported in this study may be mediated by interactions with the same polyQ proteins that interact with WT ZEBRA.…”
Section: Discussionmentioning
confidence: 53%
“…Expanded polyQ tracts can interact with polyQ-containing or other transcription factors and cofactors and thus interfere with their normal function. Target proteins can be sequestered by polyQ-protein monomers or recruited into aggregates (Kazantsev et al , 1999 ;Okazawa , 2003 ;Helmlinger et al , 2006 ;Friedman et al , 2007 ;Huang et al , 2011 ). Of note, aberrant polyQ interactions were described for CREB-binding protein, p53, Sp1, and TAFII130 and are associated with impaired transcription (Nucifora et al , 2001 ;Dunah et al , 2002 ;Bae et al , 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…A mouse model for SCA17 showed that the mutant TBP interacts with transcription factor IIB, preventing it from regulating the expression of its target gene, the small heat shock protein 1 (HSPB1) which is a potent neuroprotective factor. Furthermore, over-expression of TFIIB and HSPB1 rescued neurodegeneration [56]. It has also been shown that the mutant TBP in transgenic mouse binds to promoter DNA [57].…”
Section: )Spinocerebellarataxiatype17(sca17)mentioning
confidence: 95%